A Framework for the Relationship Between Supply Chain Risk Management and Comprehensive Performance in Industrial Companies - Alaa Abdulameer Ahmed1 , Hassen Mzali, 2, Boudrigua Abdelkader 3 (International Journal of Innovative and Applied Finance, 2024)
This research examines the relationship between supply chain risk management and the comprehensive performance of industrial companies. To achieve this goal, the study develops a theoretical model based on the previous theories, The study was applied in the General Company for the Automotive Industry in Iraq. The senior and middle administrations were selected as a sample. A structural model was built and tested through regression analysis and structural equation modeling. The research reached a set of conclusions, the most important of which are: the adoption of an effective strategy to manage the risks of the supply chain leads to a reduction in risks, an increase in the ability to control them, and an improvement in effectiveness and flexibility, which is reflected positively on performance.